Phototrophic growth of Rubrivivax gelatinosus in poultry slaughterhouse wastewater - Ponsano, Elisa Helena Giglio [UNESP]; Paulino, Clariana Z. [UNESP]; Pinto, Marcos Franke [UNESP] (Elsevier B.V., 2008)
Rubrivivax gelatinosus was grown in Pfennig's synthetic medium (PM) and in treated wastewater from poultry slaughterhouse (TW) to assess growth profiles for biomass production. Cultures inoculated at 1% (v/v) were grown under anaerobiosis at 30 +/- 2 degrees C and 1400 200 lux for 12 days. Regular absorbance curves for R. gelatinosus were found both on PM and TW. on PM, the highest dry weight of biomass, 0.39 g L-1. was achieved in the 216-h culture and the highest specific growth rate of 0.2960 h(-1) occurred in the 24-h culture. on TW, the highest biomass of 0.57 g L-1 was also obtained in the 216-h culture and the highest specific growth rate, 0.1970 h(-1), was achieved in the 48-h culture. For productivity and chemical oxygen demand investigations, the cultivation was accomplished in the TW under anaerobiosis at 32 +/- 2 degrees C and 4000 +/- 500 lux, for 10 days. Productivity was 0.085 g biomass (d.w.) L-1 day(-1), with a COD decrease of 91%. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: biomass; dry weight; absorbance; productivity; chemical oxygen demand